2023
DOI: 10.3390/ijms241210187
|View full text |Cite
|
Sign up to set email alerts
|

Isoespintanol Antifungal Activity Involves Mitochondrial Dysfunction, Inhibition of Biofilm Formation, and Damage to Cell Wall Integrity in Candida tropicalis

Orfa Inés Contreras Martínez,
Alberto Angulo Ortíz,
Gilmar Santafé Patiño
et al.

Abstract: The growing increase in infections caused by C. tropicalis, associated with its drug resistance and consequent high mortality, especially in immunosuppressed people, today generates a serious global public health problem. In the search for new potential drug candidates that can be used as treatments or adjuvants in the control of infections by these pathogenic yeasts, the objective of this research was to evaluate the action of isoespintanol (ISO) against the formation of fungal biofilms, the mitochondrial mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Given that the cell wall plays a crucial role in maintaining cellular osmotic integrity, any damage to it triggers various responses [99], previous studies have shown that inhibiting β-(1,3)-glucan synthesis leads to compensatory chitin synthesis and alterations in wall macromolecule arrangements in C. albicans. Similarly, C. tropicalis has been shown to activate a chitin compensatory response upon exposure to D-limonene [98] and ISO [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the cell wall plays a crucial role in maintaining cellular osmotic integrity, any damage to it triggers various responses [99], previous studies have shown that inhibiting β-(1,3)-glucan synthesis leads to compensatory chitin synthesis and alterations in wall macromolecule arrangements in C. albicans. Similarly, C. tropicalis has been shown to activate a chitin compensatory response upon exposure to D-limonene [98] and ISO [84].…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, we established the efficacy of isoespintanol (ISO) against clinical Candida spp. isolates, including C. tropicalis, and elucidated its molecular targets [26,27,84]. In this study, we employ a transcriptomic approach to delineate gene expression profiles, providing insights into the intricate mechanisms underlying ISO's antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…27 Rhodamine 123 staining of B. cinerea hyphae indicated impaired mitochondrial function following 7n treatment. 28 As ROS accumulation is the most conspicuous, we evaluated the effect of treatment with 7n on cell membranes.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Furthermore, its activity against human pathogenic bacteria and yeasts has also been documented [26][27][28][29]. The cytotoxicity of this compound has been studied in the line of immortalized African green monkey kidney epithelial cells (VERO) [28], human peripheral blood lymphocytes [30] and murine macrophages (RAW 264.7) [31]. However, there are no reports on its potential against tumor cells, then we hypothesize that ISO has a cytotoxic effect against them based on the wide range of described activities.…”
Section: Introductionmentioning
confidence: 98%
“…Chemical and biological activities such as antioxidant [19], anti-inflammatory [20], antispasmodic [21], vasodilator [22] and cryoprotective of canine semen, has been reported for this compound [23], as well as insecticidal [24] and antifungal activities against Colletotrichum [25]. Furthermore, its activity against human pathogenic bacteria and yeasts has also been documented [26][27][28][29]. The cytotoxicity of this compound has been studied in the line of immortalized African green monkey kidney epithelial cells (VERO) [28], human peripheral blood lymphocytes [30] and murine macrophages (RAW 264.7) [31].…”
Section: Introductionmentioning
confidence: 99%